Mapping the Research Landscape of Factors Affecting Earnings Management: A Bibliometric Study - Indrian Supheni; Sri Murni; Ari Kuncara Widagdo; Rahmawati Rahmawati; Eko Arief Sudaryono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: Earnings management is a practice that remains a subject of debate in accounting because it can be viewed as a financial performance management strategy or as an action that may mislead stakeholders. This study aims to identify and synthesize factors influencing earnings management practices based on published research findings. Method: A Systematic Literature Review (SLR) was used, with planning, conducting, and reporting stages. Data were obtained through a search for articles using the keyword